Pengaruh Risiko Kredit Terhadap Likuiditas Melalui Perputaran Piutang Pada PT. BPR Swadaya Anak Nagari - Mia Muchia Desda; Mai Yuliza (Universitas Warmadewa, 2021)
Credit is a loan agreement between a bank and another party that requires the borrower to repay the debt after a certain period of time with a certain interest rate. In refunding credit loans, there are often problems; if the creditor is less selective in choosing prospective debtors, bad credit will arise. The high credit risk that the bank will face will result in a high risk of the bank in fulfilling all its obligations. This study aims to determine the magnitude of credit risk on receivables turnover and its impact on liquidity partially or simultaneously at PT. BPR Swadaya Anak Nagari Simpang Empat. The population used in this study is the balance sheet and income statement of PT. BPR Swadaya Anak Nagari for the 2015-2019 period. The analytical tool used is path analysis using the SPSS application. This study indicates that simultaneously the effect of credit risk and receivable turnover has no significant effect and partially shows that credit risk has a significant effect on liquidity. In contrast, receivables turnover has a significant effect on liquidity. In addition, simultaneously, credit risk has a significant effect on receivables turnover and liquidity.